ASUHAN KEBIDANAN PADA IBU R TENTANG PENTINGNYA ASUHAN KEBIDANAN KOMPREHENSIF UNTUK MENCEGAH NYERI DAN INFEKSI PERINEUM PADA IBU POST PARTUM DI TPMB DEWI SANDRA LUBIS DI KECAMATAN MEUREUBO KABUPATEN ACEH BARAT TAHUN 2025 - Has, Neng Vivi Marlena; Asmanidar, Asmanidar; Norisa, Nanda; julianti, Rina (SINERGI : Jurnal Riset Ilmiah, 2025)
Perineal rupture is a tear that occurs in the perineum during labour. Perineal rupture occurs in almost all first deliveries and is not uncommon is subsequent deliveries. The occurrence of perineal rupture is caused by maternal factors (parity, birth spacing and babys weight), improrer delivery leadership, history of delivery. Forceps extraction, vacuum extraction, device trauma and episiotomy. Perineal rupture occurs in almost all first deliveries and is not uncommon in subsequent deliveries. This case study describes how perineal rupture occurs and its healing process in Mrs. R, a 29 year old primipara. Effort to handle or treat perineal wounds in this case are carried out by teaching how to do proper wound care, maintaining personal hygiene and providing education to increase client knowledge. Midwifery care provided can help clients accelerate the healing of perineal wounds. Comprehensive midwifery care regarding posrpartum care needs to be carried out from the time of pregnancy until later in the puerperium. Thus, the client can prevent and deal with problem that occur independently so that there are not infections or complications during the the puerperium.